2013
DOI: 10.1093/aob/mct055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic changes in flowering and morphology in response to adaptation to a high-latitude environment in Arabidopsis lyrata

Abstract: The results indicate that many potentially adaptive genetic changes have occurred during colonization; the two populations have diverged in their plastic responses to vernalization in traits closely connected to fitness through changes in many genomic areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…To distinguish between the F 2 reciprocal progenies, they are referred to as SpPl2F 2 and SpPl3F 2 . The growth conditions of the F 2 are described in Quilot-Turion et al (2013).…”
Section: Crossesmentioning
confidence: 99%
“…To distinguish between the F 2 reciprocal progenies, they are referred to as SpPl2F 2 and SpPl3F 2 . The growth conditions of the F 2 are described in Quilot-Turion et al (2013).…”
Section: Crossesmentioning
confidence: 99%
“…; Quilot‐Turion et al . ). This will likely influence the interactions of plants with their pollinators and seed herbivores (Elzinga et al .…”
Section: Introductionmentioning
confidence: 97%
“…In this context, few studies have evaluated the relationships between genetic differentiation and phenotypic plasticity of invasive plant species to novel, changing environments along wide latitudinal ranges. These studies have shown that species with low genetic variation can colonize wide latitudinal ranges due to high plasticity levels, sometimes related to polyploidy and hybridization, and their spread into dissimilar environments can lead to genetic differentiation (Counts, ; De Kort et al., ; Meyerson et al., ; Quilot‐Turion et al., ; Zhao, Yang, Xi, Gao, & Sun, ). For example, the high level of epigenetic changes recorded in invasive Spartina anglica (Parisod et al., ; Salmon, Ainouche, & Wendel, ) has been related to its high levels of morphological plasticity and its large ecological amplitude (Thompson, McNeilly, & Gay, ), contrasting with low interindividual genetic diversity (Ainouche, Baumel, & Salmon, ; Ayres & Strong, ; Baumel, Ainouche, & Levasseur, ).…”
Section: Introductionmentioning
confidence: 99%